2020
DOI: 10.1111/iej.13458
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental factors and mortality

Abstract: Aim To study whether oral parameters such as endodontic infections, root canal fillings, number of teeth or wearing removable dentures at baseline are associated with cardiovascular-and all-cause mortality in a follow-up of approximately 8 years. Methodology The Finnish Parogene cohort consists of 508 Finnish adults (mean age 63.3 years, SD 9.1) with cardiac symptoms, all of whom had undergone coronary angiography for accurate baseline coronary status. Extensive clinical and radiographic oral examinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…The authors of the letter make a valid point that these might affect gingival bleeding. However, our main analyses were adjusted for the periodontal inflammatory burden index (Lindy et al 2008), which is based on the number of deepened periodontal pockets, not bleeding on probing. Also, no statistically significant differences (Student's t-test) were observed in the bleeding on probing values when comparing users to nonusers for any of the three abovementioned medications.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the letter make a valid point that these might affect gingival bleeding. However, our main analyses were adjusted for the periodontal inflammatory burden index (Lindy et al 2008), which is based on the number of deepened periodontal pockets, not bleeding on probing. Also, no statistically significant differences (Student's t-test) were observed in the bleeding on probing values when comparing users to nonusers for any of the three abovementioned medications.…”
Section: Dear Editormentioning
confidence: 99%
“…We are grateful for the opportunity to reply to the concerns raised by Dr. Wu and colleagues in their letter regarding our recent publication titled ‘Association between dental factors and mortality’ (Liljestrand et al . 2020). The responses to the four remarks are listed below in the corresponding order as they appeared in the letter.…”
mentioning
confidence: 99%
“…Periodontal diseases, one of the major causes of tooth loss [5,6], was found to be significantly associated with cardiovascular diseases [7], diabetes and the related healthcare expenditure [8,9]. Recent reports have demonstrated that dental factors, such as the accumulation of oral health symptoms, or having severe tooth loss could serve as a significant predictor for mortality [10][11][12][13]. Elderly with less than functional dentition, weak chewing ability, or having difficulty in eating or swallowing later developed physical frailty (a geriatric syndrome manifested by fatigue, diminished strength, and reduced physical functioning leading to dependency or death [14]) and other adverse health outcome including mortality [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to investigate whether having fewer NoT imposes a higher risk in mortality. We tested such hypotheses using three groups of [20][21][22][23][24][25][26][27][28][10][11][12][13][14][15][16][17][18][19][0][1][2][3][4][5][6][7][8][9], edentulism and without functional dentition (NoT < 19).…”
mentioning
confidence: 99%
“…We read with great interest the study by Liljestrand et al . (2020) evaluating the association between oral parameters at baseline with cardiovascular mortality and all‐cause mortality in a follow‐up of approximately 8 years, which demonstrated that number of missing teeth appeared to be the strongest predictor of mortality, and signs of professional intervention such as root canal fillings and removable dentures appeared to be associated with improved survival. After reading this article carefully, we would like to make the following suggestions:…”
mentioning
confidence: 99%